Procedural legal transaction as an instrument of private autonomy in procedural relations (Research, Society and Development, 2025)
The present study analyzes the procedural legal transaction as an instrument for modernizing Brazilian civil procedure under the Civil Procedure Code of 2015. The research starts from the premise that the new code brought a paradigm shift by allowing the parties to take a more active role in conducting the proceedings through procedural agreements that adapt the procedure to the specific circumstances of each case. The study was developed using a qualitative method and a bibliographic and case law approach, drawing on doctrinal works and decisions from the Superior Court of Justice particularly REsp 1.738.656/RJ and REsp 1.810.444/SP to understand the limits and possibilities of private autonomy within civil procedure. It discusses how the 2015 Code broke with the previous publicist model by introducing a general clause that expanded the parties’ negotiating power while maintaining judicial control as a safeguard for legality and procedural justice. It is concluded that the procedural legal transaction represents significant progress toward greater efficiency and cooperation in civil proceedings, provided it is used within legal and constitutional limits, balancing the parties’ freedom to negotiate with the public function of jurisdiction.